2021
DOI: 10.20396/bjos.v20i00.8664073
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of the sealing ability of two calcium silicate based sealers and a resin epoxy-based sealer through scanning electron microscopy and bond strength

Abstract: Aim: this study aimed to compare the sealing ability of two types of commercially available calcium silicate bioceramic based root canal sealers and a resin based root canal sealer. Methods: Twenty one single-rooted teeth were used, samples (n= 21) were randomly divided into three groups according to the sealer used (group A; ADSEAL, group B; Wellroot, group C; Ceraseal). Roots were then cleaved longitudinally in the labiolingual direction; all samples were then sectioned at three, six, and nine mm from the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Also, other studies came up with the same conclusion while investigating the premixed TotallFill, relating their results to the small size particle, followability and expansion of the premixed bioceramic sealer allowing it to penetrate into the dentinal tubules while AH Plus sealer is mild acidic pH which could etch dentin slightly, thereby improving sealer dentin adaptation (Salem et al, 2019). Similarly, Abdelrahman et al rendered the non-significant outcome to the alkaline nature of the calcium silicate-based sealers properties, low film thickness, dimensional stability and denaturation of the dentin collagen which could collectively facilitate the sealer penetration and adaptation to root canal dentin (Abdelrahman & Hassan, 2021). Moreover, another study found no significant difference between iRoot SP pre-mixed sealer (Henry Schein, Hong Kong) and AH Plus as iRoot SP generates interlocking with dentinal tubules lead to strength and more resistance to microleakage while AH Plus had high flowability (Wang et al,2018).…”
Section: Discussionmentioning
confidence: 99%
“…Also, other studies came up with the same conclusion while investigating the premixed TotallFill, relating their results to the small size particle, followability and expansion of the premixed bioceramic sealer allowing it to penetrate into the dentinal tubules while AH Plus sealer is mild acidic pH which could etch dentin slightly, thereby improving sealer dentin adaptation (Salem et al, 2019). Similarly, Abdelrahman et al rendered the non-significant outcome to the alkaline nature of the calcium silicate-based sealers properties, low film thickness, dimensional stability and denaturation of the dentin collagen which could collectively facilitate the sealer penetration and adaptation to root canal dentin (Abdelrahman & Hassan, 2021). Moreover, another study found no significant difference between iRoot SP pre-mixed sealer (Henry Schein, Hong Kong) and AH Plus as iRoot SP generates interlocking with dentinal tubules lead to strength and more resistance to microleakage while AH Plus had high flowability (Wang et al,2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a bioceramic-based root canal sealer was used in the current case due to its excellent bioactivity, biocompatibility, and sealing capacity in the root canals, as a hermetic seal is warranted for an excellent long-term prognosis of endodontically treated teeth. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…CSC sealers including Ceraseal, EndoSequence BC, EndoSeal MTA, and BioRoot RCS, exhibited higher bond strengths compared to resin-based sealers like ADSEAL and RealSeal [11,22]. This difference is likely attributed to intrafibrillar apatite deposition.…”
Section: Csc Sealersmentioning
confidence: 96%
“…On the other hand, nine articles utilized SEM, offering a valuable means of assessing the sealing capacity and adhesion of the sealer to the walls of the root dentin. SEM provides high magnification, enabling a detailed observation of surface morphology [11]. Furthermore, CLSM made an appearance in a single article.…”
Section: Adhesive Strength Testmentioning
confidence: 99%
See 1 more Smart Citation